A phase III randomized trial evaluating chemotherapy followed by pelvic reirradiation versus chemotherapy alone as preoperative treatment for locally recurrent rectal cancer – GRECCAR 15 trial protocol. (10th June 2021) - Denost, Quentin; Frison, Eric; Salut, Cécile; Sitta, Remy; Rullier, Anne; Harji, Deena; Maillou‐Martinaud, Helene; Rullier, Eric; Smith, Denis; Vendrely, Veronique; ,
Abstract: Aim: Treatment strategies in locally recurrent rectal cancer (LRRC) are complex and need to be balanced against previous treatments received for the primary rectal cancer. Radiotherapy is an important component of treatment in LRRC. However, there is little high‐quality evidence on the role of reirradiation in this cohort. Therefore, the aim of this trial is to assess the efficacy of neoadjuvant chemotherapy followed by pelvic reirradiation versus neoadjuvant chemotherapy alone on the rate of curative surgery (R0) in previously irradiated patients with LRRC. Method: GRECCAR 15 is a prospective, multicentre, open‐label, outcome assessor‐blinded, superiority randomized controlled phase III clinical trial comparing neoadjuvant chemotherapy followed by pelvic reirradiation versus neoadjuvant chemotherapy alone in patients with LRRC previously irradiated for the primary cancer. Adult patients (>18 years old) with a histologically proven resectable LRRC, who have previously received pelvic radiotherapy for their primary rectal cancer at a dose of 25–50.4 Gy, and an Eastern Cooperative Oncology Group performance status of <2 will be eligible to participate. The pelvic reirradiation will consist of conformational intensity‐modulated external irradiation, delivering a dose of 30.6 Gy with concomitant chemotherapy using capecitabine. The primary outcome of this trial is the R0 resection rate. Overall, GRECCAR 15 aims to recruit 186 patients to detect an absolute difference of 20% in the R0 resection rate with 80% power and 5% two‐sided significance level. Conclusion: The GRECCAR 15 trial is the first, definitive, phase III trial to investigate reirradiation in LRRC. The results of this trial will inform definitively the neoadjuvant treatment strategy in previously irradiated patients and assess whether there is any associated benefit of reirradiation in combination with induction chemotherapy in improving R0 resection rates.